Impact of Preoperative Neutrophil to Lymphocyte Ratio and Postoperative Infectious Complications on Survival After Curative Gastrectomy for Gastric Cancer: A Single Institutional Cohort Study. Issue 11 (March 2016) - Mohri, Yasuhiko; Tanaka, Koji; Toiyama, Yuji; Ohi, Masaki; Yasuda, Hiromi; Inoue, Yasuhiro; Kusunoki, Masato
Abstract : Abstract: Although postoperative complications are associated with a poor long-term prognosis after resection of several solid tumors via an undetermined mechanism, there are few related reports in gastric cancer patients. Preoperative elevated neutrophil to lymphocyte ratio (NLR) reflects a systemic inflammatory response and is a predictor of poor survival in gastric cancer. The relationship between preoperative NLR and postoperative complications and the impact of these 2 factors on survival in gastric cancer remains unclear. Our aim is to examine the association between postoperative complications and survival, and preoperative NLR in patients undergoing curative resection for gastric cancer. We enrolled a total of 404 consecutive patients with gastric cancer undergoing curative gastrectomy between January 1, 2000 and December 31, 2011. Multivariable analyses were performed to correlate preoperative and operative variables with postoperative complications and to correlate complications with long-term survival after gastrectomy. Postoperative infectious and noninfectious complication rates were 17.6% and 7.9%, respectively. Preoperative NLR independently predicted the development of postoperative infectious complication, but not the development of postoperative noninfectious complications after gastrectomy. Both elevated NLR and postoperative infectious complication were independently associated with long-term survival. Also, patients with both elevated NLR and the development of postoperative infectious complication had the worst long-term survival. NLR independently predicted the development of postoperative infectious complication and lower survival after gastrectomy. Elevated NLR could trigger postoperative infectious complication and increase the risk of recurrence in patients with postoperative infectious complication after gastrectomy.